(untitled) (The Review of Diabetic Studies, 2024)
Background: Type 2 diabetes mellitus (TIIDM) is a metabolic disorder in which the level of glucose is elevated in the blood as a consequence of insulin resistance. Spexin (SPX) is a peptide involved in the regulation of blood glucose and lipid metabolism. Aims: The study aims were targeting the pathophysiology of TIIDM in postmenopausal women (PMW), where it focused on the evaluation of SPX levels in the serum of TIIDM-PMW. Results: There was a significant (P<0.001) difference in waist circumference and waist-to–to-‎height ratio between TIIDM and non-diabetic PMW, which indicates more ‎central fat in patients. FSG, HbA1c, insulin, and HOMA-IR levels were elevated ‎significantly in TIIDM PMW, indicating poor glycemic control. SPX ‎and SOD levels were significantly reduced in TIIDM patients, while MDA, CRP, and IL-6 ‎levels were significantly increased, reflecting oxidative stress and ‎inflammation. The lipid profile was changed significantly in TIIDM PMW. ‎Moreover, the correlation in TIIDM PMW indicated a positive ‎association between SPX and MDA, SPX and age, CRP and IL-6, CRP and age, IL-6 and ‎FSG, SOD and insulin, and a negative association between SPX and waist-to-height ratio, ‎SPX and FSG, SPX and HOMA-IR, and MDA and insulin. At last, SPX has shown ‎excellent sensitivity in the prognosis of TIIDM in PMW. ‎Conclusion: SPX has been shown to play an important role in the pathophysiology of TIIDM in PMW. Targeting SPX may provide a novel technique to maintain good glycemic control in diabetic patients.